The Drosophila ubiquitin-specific protease Puffyeye regulates dMyc-mediated growth - Li, Ling (Company of Biologists, 2013)
The essential and highly conserved role of Myc in organismal growth and development is dependent on the control of Myc protein abundance. It is now well established that Myc levels are in part regulated by ubiquitin-dependent proteasomal degradation. Using a genetic screen for modifiers of Drosophila Myc (dMyc)-induced growth, we identified and characterized a ubiquitin-specific protease (USP), Puffyeye (Puf), as a novel regulator of dMyc levels and function in vivo. We show that puf genetically and physically interacts with dMyc and the ubiquitin ligase archipelago (ago) to modulate a dMyc-dependent cell growth phenotype, and that varying Puf levels in both the eye and wing phenocopies the effects of altered dMyc abundance. Puf containing point mutations within its USP enzymatic domain failed to alter dMyc levels and displayed no detectable phenotype, indicating the importance of deubiquitylating activity for Puf function. We find that dMyc induces Ago, indicating that dMyc triggers a negative-feedback pathway that is modulated by Puf. In addition to its effects on dMyc, Puf regulates both Ago and its cell cycle substrate Cyclin E. Therefore, Puf influences cell growth by controlling the stability of key regulatory proteins.